MANGROVES FOR NATIONAL DEVELOPMENT AND CONSERVATION IN INDONESIA: CHALLENGES FOR THE FUTURE - Sukardjo, Sukristijono (Marine Research in Indonesia, 2009)
Indonesias mangrove resources (soils and waters, flora and fauna, and as an ecosystem all are called as mangrove biodiversity) are growing in importance. As a consequence of past and present human utilization the mangrove resources have been depleted. Keen competition for use of the mangrove resources is apparent and is likely to intensify in the future. This policy document stresses the importance of mangroves for the Nation and the need for the Government to manage and protect them. A set of basic principles for the management and protection of mangroves is provided, together with an outline of some actions which local and central governments (Pemerintah Pusat dan Daerah) should take up in order to achieve a balance between the use of mangrove resources, their conservation and long term national development.